2022
DOI: 10.3390/jfb14010002
|View full text |Cite
|
Sign up to set email alerts
|

Polydopamine-Coated Alginate Microgels: Process Optimization and In Vitro Validation

Abstract: In the last decade, alginate-based microgels have gained relevant interest as three-dimensional analogues of extracellular matrix, being able to support cell growth and functions. In this study, core-shell microgels were fabricated by self-polymerization of dopamine (DA) molecules under mild oxidation and in situ precipitation of polydopamine (PDA) onto alginate microbeads, processed by electro fluid dynamic atomization. Morphological (optical, SEM) and chemical analyses (ATR-FTIR, XPS) confirmed the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Viscosity (η, Pa•s) and viscoelastic properties play a crucial role in the EFDA to process the polymer solutions, affecting the morphology of microparticles [34]. For instance, the higher viscosity of solutions generates larger and spherical microparticles, while lower viscosities generate smaller particles [35].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Viscosity (η, Pa•s) and viscoelastic properties play a crucial role in the EFDA to process the polymer solutions, affecting the morphology of microparticles [34]. For instance, the higher viscosity of solutions generates larger and spherical microparticles, while lower viscosities generate smaller particles [35].…”
Section: Resultsmentioning
confidence: 99%
“…After collecting particles, they were observed using a confocal microscope. Additionally, core/shell circularity of microgels was evaluated according to previous studies [ 34 ] using a customized image analysis procedure—i.e., adjustment of the image threshold to remark the core/shell interface and measurement of the shape factor of the inner core/outer shell using the following equation: C = 4π(A/P 2 ) where A is the area, and P is the perimeter. For an ideal sphere, C = 1.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have focused on the idea that regenerative processes can be supported and accelerated by electrical stimuli which can facilitate the repair of the injured tissues [40]. For this purpose, the use of intrinsically electroconductive polymers is rapidly growing for different biomedical applications, from medicine to biosensing [49,50,88]. In this view, the fabrication of PVA fibers by integrating material phases with different electroconductive properties was preliminarily investigated (i.e., PVP and PEDOT:PS) (Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…In this view, incorporating electroactive phases-i.e., conductive polymers (CPs)-into PVA fibers can be a promising strategy to support the electroconductive mechanisms that regulate cellular adhesion and proliferation. To date, various CPs such as polypyrrole (PPy), poly(3,4-ethylene dioxythiophene) (PEDOT, conductivity up to 10 3 S/cm [44]), and polyaniline (PANi) were found to be particularly suitable for biomedical use [45][46][47] and electrospinning was successfully employed for the manufacture of composite or blended fibers based on CPs [48][49][50]. Moreover, polyvinylpyrrolidone (PVP) has been studied before in order to improve the conductive properties of PVA as polymer coatings around 0.30 S/cm [51] and there are studies reported in the literature that focused on the effects of CPs to promote the regeneration of electroactive tissues (i.e., muscles, nerves, brain) [52].…”
Section: Introductionmentioning
confidence: 99%
“…This makes them suitable for a wide range of applications in fields such as electronics, energy storage, and sensing [1][2][3]. In this context, research efforts have focused on exploring the properties and potential of various electroconductive polymeric composites and developing new methods for their synthesis and characterization for biomedical use [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%